Climate Controversy Under the Subjection of Forest Depopulation in the Jungle Eyebrow of Huanuco and Ucayali — Peru - Valdiviezo Delgado, Cristian Kengi (2025)
Anthropogenic activities uneven climate balance. Deforestation is an environmental problem resulting from human activities that affect the climate and its variables. Huanuco and Ucayali are provinces of Peru located in the upper jungle of the Amazon and have high rates of deforestation with 347,583.96 and 267,899.76 hectares of forests lost in the last 21 years due to activities such as oil palm planting, and others. In the present investigation, it is investigaded the existence of a statical correlation between climate variability and deforestation. Likewise, the state of the forests. In 2009, the temperature presented high peaks, with 31.43°C indicating a direct relationship with deforestation since in previous years it was deforested on a large scale. Likewise, in 2014 the study area reached the peak of deforestation in the 21 years analyzed with a total of 149,217.70 hectares of forests, which caused that in 2015 the temperature reached high figures again. 2020 is the second year with the highest deforestation, losing 146,743.83 hectares of forests and consequently presented a minimum temperature of 26°C, unlike previous years with 21.17°C, which in the long term would cause alterations in the ecosystems of the investigated areas. Similarly, precipitation and relative humidity show similar behaviours. Finally, the statistical analysis analyzed the existence of a 95% confidence correlation between climate variability and deforestation.